2015
DOI: 10.1152/jn.00233.2014
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for distinct brain networks in the control of rule-based motor behavior

Abstract: Granek JA, Sergio LE. Evidence for distinct brain networks in the control of rule-based motor behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 105 publications
3
10
0
Order By: Relevance
“…Indeed, recent anatomical studies have found altered diffusion characteristics within white matter tracts in concussed adolescents, younger and older adults with concussion history exactly in those pathways connecting frontal and parietal regions [ 29 , 54–56 ]. Again, these data are in line with our group's findings on the crucial role played by such fronto-parietal networks in integrating thought and action [ 26 , 28 , 32 , 57 ].…”
Section: Resultssupporting
confidence: 91%
“…Indeed, recent anatomical studies have found altered diffusion characteristics within white matter tracts in concussed adolescents, younger and older adults with concussion history exactly in those pathways connecting frontal and parietal regions [ 29 , 54–56 ]. Again, these data are in line with our group's findings on the crucial role played by such fronto-parietal networks in integrating thought and action [ 26 , 28 , 32 , 57 ].…”
Section: Resultssupporting
confidence: 91%
“…Observations of white matter abnormalities reported in retired NHL players [ 36 ], adult female athletes [ 39 ] and youth athletes [ 40 ] could provide an explanation for observations of increased brain activity post-concussion. We postulate that in the present study, where these athletes’ brains have ostensibly recovered from mild injury, there may still be deficits in the connections between areas required to successfully integrate thought and action [ 24–25 , 30 , 41–44 ]. That is, we suggest that our observed behavioral deficits may be related to underlying changes in the frontoparietal networks necessary for the successful integration of thought and action, and likely these cortical networks’ interactions with subcortical brain areas, for example, the cerebellum [ 24 , 29–30 , 41–43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cerebellum -responsible for motor coordination, motor learning, and spatial attention (18,52), and often not accounted for in this field of research -also plays an essential role in both standard and non-standard reaching tasks (13,53,54). Increased cerebellar activity has been noted in non-standard compared to standard visuomotor tasks, resulting from the need for corrective movements or possibly due to a role in the actual dissociation of eye and hand (18).…”
Section: Discussionmentioning
confidence: 99%
“…Of the final components, we identified four a priori-selected resting state fMRI networks: the Default Mode Network (DMN), the Dorsal Attention Network (DAN), the frontoparietal network (FP), and the anterior cerebellar network (31,32) which are additionally known to be involved in CMI tasks (13,18) and commonly impacted by concussion (14,16,33). The group level results from MELODIC were input into a dual regression analysis within FSL that was utilized to backproject spatial maps and individual time series for each component and subject.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation